MicroRNA‐222 promotes colorectal cancer cell migration and invasion by targeting MST3. Issue 5 (2nd April 2019) - Luo, Fei; Zhou, Jianfeng; Wang, Shihua; Sun, Zhao; Han, Qin; Bai, Chunmei
Abstract : Metastasis is one of the major causes of death in colorectal cancer (CRC) patients. MiR‐222 has been reported to be an oncogene in many types of cancer. However, its role in CRC cell invasion and migration as well as CRC downstream signaling pathways remains largely unknown. Our study found that miR‐222 overexpression promotes the migration and invasion of CRC cell lines, and miR‐222 interference results, as expected, in inhibition of migration and invasion. Bioinformatic analysis and dual luciferase reporter assay showed that mammalian STE20‐like protein kinase 3 ( MST3 ) may be the target gene of miR‐222. Down‐expression of MST3 in CRC cell lines enhanced their migration and invasion, but overexpression of MST3 could attenuate miR‐222 overexpression in the promotion of migration and invasion in colorectal cell lines. HCT116 cell lines overexpressing miR‐222 were transplanted into nude mice resulting in more lung metastases than in the control group. Further study found that MST3 may play a role in paxillin phosphorylation to reduce adhesion, or increase the invadopodia. These findings demonstrate that miR‐222 modulates MST3 and therefore plays a critical role in regulating CRC cell migration and invasion. Thus, miR‐222 may be a novel therapeutic target for CRC. Abstract : MiR‐222 may enhance colorectal cancer cell migration and invasion by down‐regulating MST3. MST3 may decrease migration and invasion through the regulation of invadopodia formation via increased paxillin phosphorylation.